Learning Disabilities and Epilepsy: About a Clinical Case - Carolina Freitas Fernandes; Carolina Ferreira Gonçalves; Paulo Rego Sousa (Gazeta Médica, 2023)
Landau-Kleffner syndrome (LKS) is an epilepsy syndrome of childhood, characterized by auditory verbal agnosia and severe electroencephalographic abnormalities. It happens between 3-7 years of age, 20% without seizures. A 6-years-old boy, with normal psychomotor development, who begins to experience difficulties in understanding the meaning of words, sometimes with incoherent speech and writing difficulties (irregular handwriting, spelling mistakes). Neurological evaluation showed loss of comprehensive language with auditory verbal agnosia, difficulties in fine motor skills and in graphomotor coordination. After clinical suspicion, the diagnosis of SLK was confirmed by night video-electroencephalogram (EEG): abundant paroxysmal activity of bilateral and independent fronto-center-temporal spikes and spike-wave activity, with an almost continuous exacerbation during sleep. Initially treated with valproate and clobazam, without improvement, he started prednisolone, with improvement in language, writing and normalization of the EEG. Knowledge of this syndrome is important for differential diagnosis with other neurological disorders, especially learning difficulties.